Efecto citotóxico de las semillas de Annona cherimola en cultivos de cáncer de cérvix, mama y leucemia mieloide crónica - Quispe Mauricio, Angel (2009)
Introduction: Diverse natural products of the Annona genus has been used in the treatment of the cancer. Annona cherimola has diverse pure compounds of its seeds and stems that have demonstrated antitumor activity against nasopharyngeal carcinoma.   Objective: To determine the cytotoxic effect of the Annona cherimola seed extract on the cell lines MCF-7 (Human breast adenocarcinoma), ME-180(epidermal carcinoma of the cervix), K562 (chronic myeloid leukemia) and 3T3 (normal mouse fibroblasts).   Materials and methods: The lines MCF-7, ME-180, K 562 and 3T3, were exposed to four concentrations of the Annona cherimola seed ethanolic extract (0.125, 0.031, 0.008, 0.002mg/mL), also to different concentrations of 5-fluorouracil (5-FU) (0.01563, 0.00391, 0.00098, 0.00024mg/mL) and Cisplatin (0.00250, 0.00063, 0.00016, 0.00004mg/ mL) which were used as a positive controls. Percentage growth was assessed after 48 hours. The growth inhibitory concentration 50 (CI50) was determined using linear regression analysis; also we obtained the coefficients of determination r2 using Microsoft Office Excel 2007. Finally the Selectivity Index of each sample was determined.   Results: The CI50 in μg/mL of the Annona cherimola seed ethanolic extracts were 9.4(r2 = 0.96) for MCF-7; 6.6(r2 = 0.99) for ME-180; 2.2 (r2 = 0.96) for K562 and 29.5(r2 = 0.98) for 3T3. The CI50 of 5-FU were 3.4(r2 = 0.95) for MCF-7; 3.8(r2 = 0.96) for K562 and 0.2(r2 =0.98) for 3T3 and the CI50 of Cisplatin were 12.1(r2 = 0.96) for MCF-7; 0.1(r2 = 0.96) for K562 and 0.3(r2 = 0.99) for 3T3. The dose-response relationship of the extract to the 3T3 cell line was -0.98 (p<0.05) and for the K562 tumor cell line was -0.98 (p<0.05). The extract selectivity index were 2.17, 6.07 and 2.39 for the MCF-7, K562 and ME-180 cell lines, respectively; On the contrary, the 5-FU and Cisplatin, only reached values of 0.07 and 0.06; 0.02 and 2.25 for the lines MCF-7 and K562 respectively.   Conclusions: The cytotoxic profile of the Annona cherimola seed etanolic extract is very encouraging by its high citotoxicity against tumor cells and low citotoxicity against normal cells; surpassing, drugs widely known like 5-FU and Cisplatin in selectivity index.